ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA KOPERASI SAE PUJON KABUPATEN MALANG - Sa'adah, Lailatus; Widyawati, Widyawati; Murtingtyas, Triana (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2023)
The purpose of this study is to analyze financial reports and determine bankruptcy using the Z-Score method. The financial ratios in this study are the ratios of liquidity, profitability, solvency and profitability. This research was conducted at the SAE Pujon Cooperative with samples of balance sheets and income statements and used a quantitative descriptive research method. The data collection for this study used a descriptive analysis technique, namely comparing data from 2019 - 2021. Based on the results of the research, it can be seen that the level of liquidity ratios in the SAE cooperative is in liquid condition, namely in good condition as measured by the Current Ratio, Cash Ratio, and Quick Ratio. The level of profitability as measured by Gross Profit Margin, Net Profit Margin is considered efficient. The level of solvency is measured using the Debt To Asset Ratio and the Debt To Equity Ratio is assessed as Solvable. The level of profitability is measured using Return On Assets and Return On Equity is assessed as Profit